7+1x=6

Simple and best practice solution for 7+1x=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+1x=6 equation:


Simplifying
7 + 1x = 6

Solving
7 + 1x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 1x = 6 + -7

Combine like terms: 7 + -7 = 0
0 + 1x = 6 + -7
1x = 6 + -7

Combine like terms: 6 + -7 = -1
1x = -1

Divide each side by '1'.
x = -1

Simplifying
x = -1

See similar equations:

| B=-6 | | 4x+10=120-9x | | -3x+44=x+20 | | 3x-9=x+1 | | 20=-4(5-m) | | 10.8x^8*.5x^2= | | 3x+12=102-6 | | 2+(4.5)= | | 6x+3-8x=-21 | | 5p+5t= | | 5(y+2)=3y-4+y | | (6-2x)(-5)= | | 4B-32B=36B-8BY | | 6x-2-x=13 | | 11x+19=5x+1 | | 116-4x=32x+24 | | 24x^2+17x+3=0 | | 2(3y-5x)= | | x^20= | | 4x-5=2x+8 | | -2+18d=19d+10 | | -6a(a+3)= | | 5n-2=-2n+1 | | 4r-8r+8+r= | | 36-6y=18x-6 | | x^2+10+23=0 | | -18+54X=27 | | 14x^2+17x-6= | | Y=[[x+5]] | | 8(b-3)= | | 5x+2xw=7-4xy | | -3(2x-4)=8x |

Equations solver categories